Political Budget Cycles in Papua New Guinea - Faal, Ebrima (Washington, D.C. : International Monetary Fund, 2007)
This paper assesses the presence of opportunistic electoral budget cycles in Papua New Guinea. Using quarterly time series data, a clear pattern emerges of pre-election manipulations of fiscal policy by incumbent governments, mainly in the form of increased development spending and overall primary expenditure, followed in some cases by retrenchment in post-election periods. These findings are consistent with the predictions of rational opportunistic political business cycle theory. It is noteworthy that revenue was not statistically significantly related to elections, either in the pre- or post-election period. In this regard, electoral swings in fiscal deficits reflect a preference for influencing expenditures rather than taxation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet